Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1074/jbc.m112.399782
|View full text |Cite
|
Sign up to set email alerts
|

Specificity Protein 1 (Sp1)-dependent Activation of the Synapsin I Gene (SYN1) Is Modulated by RE1-silencing Transcription Factor (REST) and 5′-Cytosine-Phosphoguanine (CpG) Methylation

Abstract: Background: Syn I plays a key role at presynaptic terminals.Results: Sp1 binds to the SYN1 promoter, activating its transcription.Conclusion: Sp1 is a novel regulator of SYN1 transcription, whose activity is inhibited by REST and CpG methylation.Significance: Elucidating the mechanisms underlying basal activation of neuron-specific genes is fundamental to understand brain pathologies, where transcription is often dysregulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 56 publications
(61 reference statements)
2
36
0
Order By: Relevance
“…We previously found that differentiation of N2a cells induced by retinoic acid (RA) treatment is associated with loss of endogenous REST activity and increased expression of its target genes (28). Indeed, we found that neurite outgrowth was enhanced in differentiating N2a cells transfected with the open form of the AsLOV2-PAH1b with respect to the cells expressing the closed form of the chimera (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…We previously found that differentiation of N2a cells induced by retinoic acid (RA) treatment is associated with loss of endogenous REST activity and increased expression of its target genes (28). Indeed, we found that neurite outgrowth was enhanced in differentiating N2a cells transfected with the open form of the AsLOV2-PAH1b with respect to the cells expressing the closed form of the chimera (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…2F). Similarly, when the AsLOV2-PAH1b constructs were expressed in N2a cells, the transcription of the endogenous SYN1, NAV1.2, and BDNF genes, which are well-known REST targets (9,28), was significantly up-regulated only in cells containing the open chimera (Fig. 2G).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Finally, we confirmed that CREB and Nurr1 are active enhancers of SYN1 and SYN2 promoter activities. Other transcription factors have been recently identified to positively regulate SYN1 promoter activity, including Sp1 at sites immediately distal and proximal from the proximal CREB site (64), which raises the possibility that Sp1 and CREB might cooperate to control SYN1 expression.…”
Section: Dependence On Endogenous αSyn For Exogenous O-αsyn To Inducementioning
confidence: 99%
“…Cytosine methylation-mediated interference of Sp1 binding to its cis-elements on promoters is known to inhibit the expression of several of its target genes in various tissues (2,7,17). We (23) have previously demonstrated that Sp1 activates basal ␣ENaC transcription in mIMCD3 cells and that aldosterone enhances Sp1 binding to, and trans-activation of, the ␣ENaC promoter, without altering nuclear Sp1 protein levels.…”
Section: Dnmt3b and Mbd4 Contribute To The Basal Repression Of ␣Enac mentioning
confidence: 98%